Assessing Family Functioning Before and After an Integrated Multidisciplinary Family Treatment for Adolescents With Restrictive Eating Disorders - Mensi, Martina M.; Orlandi, Marika; Rogantini, Chiara; Provenzi, Livio; Chiappedi, Matteo; Criscuolo, Michela; Castiglioni, Maria C.; Zanna, Valeria; Borgatti, Renato (Frontiers in Psychiatry, 2021)
The present study presents an investigation of family functioning in the families of adolescents with severe restrictive eating disorders (REDs) assessed before and six months after a multidisciplinary family treatment program that combined psychodynamic psychotherapy, parental role intervention, and triadic or family-centered interventions. Nutritional counseling and neuropsychiatric monitoring of the overall treatment and care process were also provided. Family functioning was assessed using the clinical version of the Lausanne Trilogue Play (LTPc), a semi-structured procedure for observing family dynamics, previously validated for this patient population. The LTPc is divided into four phases. In phase 1, the mother interacts with the patient while the father assumes the role of observer. In phase 2, the father plans an activity with the patient while the mother observes. In phase 3, all the family members interact. Finally, in phase 4, the parents talk while the adolescent observes. A significant change emerged in family functioning after the treatment, but only for the interactive phase 2, when the father is required to interact with the daughter while the mother silently observes. The results of this study suggest that a relatively brief multidisciplinary treatment program may significantly improve family functioning in the families of patients diagnosed with severe REDs. Although appropriate clinical trials are needed to further test the efficacy of this treatment, the results also reinforce the concept that treatment programs targeting the individual patient and both the parents should be a first-line approach in adolescents with severe REDs.